Exploring women's childbirth experiences and perceptions of delivery care in peri-urban settings in Nairobi, Kenya - Jackline Oluoch-Aridi; Patience. A. Afulani; Danice. B. Guzman; Cindy Makanga; Laura Miller-Graff (BMC, 2021)
Abstract Background Kenya continues to have a high maternal mortality rate that is showing slow progress in improving. Peri-urban settings in Kenya have been reported to exhibit higher rates of maternal death during labor and childbirth as compared to the general Kenyan population. Although research indicates that women in Kenya have increased access to facility-based birth in recent years, a small percentage still give birth outside of the health facility due to access challenges and poor maternal health service quality. Most studies assessing facility-based births have focused on the sociodemographic determinants of birthing location. Few studies have assessed women's user experiences and perceptions of quality of care during childbirth. Understanding women's experiences can provide different stakeholders with strategies to structure the provision of maternity care to be person-centered and to contribute to improvements in women's satisfaction with health services and maternal health outcomes. Methods A qualitative study was conducted, whereby 70 women from the peri-urban area of Embakasi in the East side of Nairobi City in Kenya were interviewed. Respondents were aged 18 to 49 years and had delivered in a health facility in the preceding six weeks. We conducted in-depth interviews with women who gave birth at both public and private health facilities. The interviews were recorded, transcribed, and translated for analysis. Braune and Clarke's guidelines for thematic analysis were used to generate themes from the interview data. Results Four main themes emerged from the analysis. Women had positive experiences when care was person-centered-i.e. responsive, dignified, supportive, and with respectful communication. They had negative experiences when they were mistreated, which was manifested as non-responsive care (including poor reception and long wait times), non-dignified care (including verbal and physical abuse lack of privacy and confidentiality), lack of respectful communication, and lack of supportive care (including being denied companions, neglect and abandonment, and poor facility environment). Conclusion To sustain the gains in increased access to facility-based births, there is a need to improve person-centered care to ensure women have positive facility-based childbirth experiences.